2013
DOI: 10.1140/epje/i2013-13001-8
|View full text |Cite
|
Sign up to set email alerts
|

Position control of desiccation cracks by memory effect and Faraday waves

Abstract: Pattern formation of desiccation cracks on a layer of a calcium carbonate paste is studied experimentally. This paste is known to exhibit a memory effect, which means that a short-time application of horizontal vibration to the fresh paste predetermines the direction of the cracks that are formed after the paste is dried. While the position of the cracks (as opposed to their direction) is still stochastic in the case of horizontal vibration, the present work reports that their positioning is also controllable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…In neither case have there been systematic studies of the effect of adsorbed proteins on the material properties. A recent study evaluated bending rigidity constants from vesicles extruded with ~40–50 nm radii, however dynamic light scattering (DLS) experiments indicated that some of the radii quickly grew to 70–80 nm [62], rendering these vesicles substantially larger than an average synaptic vesicle (~40 nm) [172]. NSE measurements were fit based on the Helfrich-like treatment of a bilayer as a thin, homogenous sheet by Zilman and Granek [61] and bending rigidities were determined via the undulation relaxation rates.…”
Section: Protein-induced Alterations In Membrane Materials Propertiesmentioning
confidence: 99%
“…In neither case have there been systematic studies of the effect of adsorbed proteins on the material properties. A recent study evaluated bending rigidity constants from vesicles extruded with ~40–50 nm radii, however dynamic light scattering (DLS) experiments indicated that some of the radii quickly grew to 70–80 nm [62], rendering these vesicles substantially larger than an average synaptic vesicle (~40 nm) [172]. NSE measurements were fit based on the Helfrich-like treatment of a bilayer as a thin, homogenous sheet by Zilman and Granek [61] and bending rigidities were determined via the undulation relaxation rates.…”
Section: Protein-induced Alterations In Membrane Materials Propertiesmentioning
confidence: 99%
“…Earlier studies have elucidated the mechanism of desiccation crack formation for various grain-liquid mixtures [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The mixtures typically consist of a skeleton of solid grains and pore spaces that are filled with either liquid or air bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…7 the fraction of broken beams is practically the cumulative probability of breaking P b (ε), which in principal could be obtained analytically from the density functions Eq. (10). Neglecting the role of bending in breaking, a linear function is obtained P b (ε) = (1/2W ε )(ε − ε th + W ε ) for ε ε th − W ε .…”
Section: Effect Of Disorder On the Breakup Processmentioning
confidence: 99%
“…Detailed experiments varying the way of excitation, furthermore, the strength and range of interaction of colloidal particles have * ferenc.kun@science.unideb.hu revealed that the memory effect of pastes provides an efficient way of controlled generation of crack patterns in thin layers. For example, by applying vertical vibration to the thin layer of paste, the position of crack formation can be controlled, because Faraday waves localize stronger horizontal vibration at node regions where cracks appear earlier than in other regions [10]. Effectiveness of memory of paste can be controlled by adding sodium chloride to paste, because the strength and range of interaction between charged colloidal particles in paste can be controlled by the screening effect [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation